Prevalence and Associated Factors of Diabetes Mellitus in Hosanna Town, Southern Ethiopia - Nebiyu Dereje; Alemu Earsido; Layla Temam; Ashenafi Abebe (Ubiquity Press, 2020)
Background/Objectives: Diabetes is a global public health problem, and its burden is rising, particularly in developing countries. However, limited data is available from sub-Sahara African communities to assess and monitor the disease burden. The study aimed to determine the prevalence and associated factors of diabetes in Hosanna, Ethiopia. Methods: A community-based cross-sectional study was conducted among 634 randomly selected adults in Hosanna. The study participants were recruited by multi-stage stratified sampling. A face-to-face interview using a structured questionnaire was administered by trained nurses. Anthropometry, blood pressure and fasting blood glucose levels were measured. Diabetes mellitus was considered when the fasting blood glucose level was ≥126 mg/dl on two separate measurements or when the participant self-reported a previous diagnosis of diabetes by healthcare providers or when the participant was currently receiving treatment for diabetes. Multi-variable binary logistic regression was used to identify factors associated with diabetes mellitus. Findings: The overall prevalence of diabetes was found to be 5.7% (95% CI; 4.0-7.7), out of which more than one third (36%) were not aware of it prior to the survey. Nearly two thirds (61.1%) of the diabetic participants were also found to be hypertensive. In the multi-variable analysis, diabetes was associated with current alcohol use, sitting on average of more than 8 hours/day, abnormal BMI and being hypertensive. Conclusion: The prevalence of diabetes among the adult population in the town is alarming. If appropriate measures to address the burden are not emplaced, it might result in serious complications to the patients and unnecessarily high costs to the health system of the country. Active screening for raised blood glucose level should be given due consideration, particularly in the community setting. Designing health education programs on the importance of physical activity and the risks of alcohol use should also be considered.